2002
DOI: 10.1177/0734904102020006670
|View full text |Cite
|
Sign up to set email alerts
|

Application of Water Mist Fire Suppression Systems in Small Retail Shops

Abstract: Protecting small retail shops packed with combustible goods by sprinkler system might not be too satisfactory. Any delay in system activation will lead to a flashover fire. Also, there might be serious water damage which is not good for shops selling expensive items. Alternative fire protection systems should be searched for. Water mist might be effective for suppressing postflashover fires if the system is designed properly. Whether water mist fire suppression systems can be used in the small shops is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Several numerical models [15][16][17] were developed to study fire plume behavior under water sprays. The smoke layers are significantly affected by water flow rate, droplet size and sprinkler locations.…”
Section: Introductionmentioning
confidence: 99%
“…Several numerical models [15][16][17] were developed to study fire plume behavior under water sprays. The smoke layers are significantly affected by water flow rate, droplet size and sprinkler locations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the possibility of using water mist in suppressing cooking oil fires in bench-scale tests with a cone calorimeter [20] and in a largerscale kitchen were led by Chow and associates [21,22]. All their results indicated that water mist can only control and extinguish cooking oil fires if designed properly [23]. However, there were risks to nearby personnel or firefighters due to vapor explosion and boilover when the water mist reached the hot oil surface.…”
Section: Introductionmentioning
confidence: 99%
“…Water mist fire suppression system may be a good choice for the retail shops (Chow, Yao and Ng, 2002). With proper design and operation, water mist system might be used effectively for suppressing post-flashover fires inside a shop.…”
Section: Cabin Designmentioning
confidence: 99%
“…Chow, Yao and Ng, 2002) should be considered. For quick fire suppression in a small retail shop, using water mist system might be a solution.…”
Section: Water Mist Fire Suppression Systemmentioning
confidence: 99%